Differentiation of the honey bee (Apis mellifera L.) antennal lobes during metamorphosis: a comparative study among castes and sexes - Roat, Thaisa Cristina [UNESP]; da Cruz-Landim, Carminda [UNESP] (Brill Academic Publishers, 2011)
In insects the antennal lobes (AL) constitute the brain deutocerebrum. In bees they consist of two neuropil regions, each associated with one antenna, delimited by a layer of glial cells and somata of neurons. The neuropil is organized in distinct globular structures of dense synaptic axons coming from the olfactory organs of the antennae, known as glomeruli. In Apis mellifera, as in other eusocial species of bees, queens, workers, and drones perform different functions in the colony and consequently the organs associated with these functions undergo a differential development. In this paper we analyzed the structure and size of the differentiating AL of queens, workers, and drones during metamorphosis using light microscopy. During metamorphosis the neuropil enlarge and differentiates into concentric structures known as glomeruli. The results showed size, structural and temporal differences in the glomeruli development among the classes of individuals of the colony. The neuropil differentiation starts early and is faster in drones and newly emerged worker is the colony individual class with greater neuropil area in AL. These results are discussed taking in account the functions of the individuals in the colony. (C) Koninklijke Brill NV, Leiden, 2011.
Keywords: Queens; workers; drones; brain; insect; antennal lobe